(untitled) (Journal of Dhaka Medical College, 2011)
Disseminated intravascular coagulation (DIC) is an acquired and complex disorder that occurs in a wide variety of clinical conditions. This is basically a state of increased propensity for clot formation triggered by a variety of stimuli related to such diverse disorders as sepsis, endothelial cell damage (heat stroke, shock), obstetrical complication (abruptio placenta, amniotic fluid embolism, severe preeclampsia and retained intrauterine dead foetus) and neoplasm. DIC is a classic complication of obstetric conditions occurring in more than 50 percent of patients with obstetric causes. In DIC, an unregulated thrombin explosion cause release of free thrombin into the circulation that leads to the clinical features of DIC, with thrombin and plasmin responsible for the thrombotic and haemorrhagic manifestations, respectively. The diagnosis and treatment of this syndrome require an understanding of its pathophysiology, awareness of the disorders that can trigger it and its early recognition. Acute DIC is usually associated with infections, the commonest cause, about 10-20% of patients with gram negative sepsis have evidence of DIC. Chronic DIC is usually associated with retained dead fetus, carcinomatosis. The diagnosis of this syndrome is essentially clinical, with laboratory tests providing confirmatory evidence. Microvascular thrombosis is the primary mechanism in most cases, and end organ failure is a major cause of death. No single diagnostic test exists for DIC. DIC is initially suggested by the following combination; a clinical condition consistent with DIC, thrombocytopenia, prolonged PT, APTT, and presence of FDP/D-dimer. Medical treatment depends on the cause of the DIC. Basically it involves removing the cause for example, delivery of placenta if it is retained or abrupted, delivery of foetus if retained, quick delivery if severe eclampsia and so on, hysterectomy if bleeding can not be controlled from placental site. After then, and/or con-currently treat DIC with blood and plasma transfusions and appropriate supportive measures. As the sequel of DIC can be devastating, early clinical suspicion and laboratory diagnosis are essential. This review article provides essential guideline for the appropriate diagnosis and clinical management of DIC in obstetric patients. Key words: Disseminated intravascular coagulation (DIC); Obstetric; Thrombosis; Fibrin; Ddimer; FDP; Anticoagulant. DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8585 J Dhaka Med Coll. 2011; 20(1) :68-74